Radiology in the Christchurch earthquake of 22 February 2011: Challenges, interim processes and clinical priorities. Issue 2 (12th February 2016) - Gregan, Jude; Balasingam, Adrian; Butler, Anthony
Abstract: Introduction: The Canterbury earthquake of 22 February 2011 initiated a mass casualty event for Christchurch Hospital, which suffered damage itself, and faced logistical difficulties in continued operation. Radiology was part of the hospital‐wide response. This paper reviews the radiology department response and surveys opinions of emergency doctors to provide an overview of events of the day and thoughts regarding any potential future response. Methods: Two main approaches were undertaken: (i) informal data gathering and discussions with staff including radiographers, sonographers, radiologists, emergency doctors and others present on the day regarding their experiences; and (ii) survey of emergency doctors regarding their experiences and recommendations. A comparison with other similar events was also conducted. Results: (1) Diagnostic radiology services were initially constrained by a lack of power and lift access. Usual imaging and reporting pathways were interrupted. Alternative processes were initiated to ensure an ongoing radiology service with available resources. Lessons were learned and changes implemented locally.(2) Survey data confirmed several primary outcomes: (i) Ultrasound was crucial while CT was down; (ii) all available imaging modalities remain important in a disaster response; and (iii) preliminary reports from radiologists in the emergency department (ED) were useful in the immediate post‐earthquake period. Conclusion: Although resources were limited, a diagnostic radiology service remained operational. The Christchurch experience reinforces the need for disaster planning and rehearsal of plans.